The minimum knowledge of Geography in the Bachelor’s degree in Primary Education - Binimelis Sebastián, Jaume; Ordinas Garau, Antoni (Revista Complutense de Educación, 2016)
The subject Social Sciences and its Didactics I (Geography) taught in the Bachelor’s degree in Primary Teacher Education is, at the University of Balearic Islands and in most Spanish universities, the only academic contact that future teachers will have with Geography. There is an atmosphere of concern for teacher training in Spain, a worry which is not exclusive of geographers or our country. This paper investigates the minimum knowledge of Geography required to future teachers through a knowledge test based, mainly, on the Social Sciences curriculum of Primary Education of the Autonomous Community of the Balearic Islands. The results obtained demonstrate that the students of Bachelor’s degree in Primary Education have not learnt these contents after their long academic career. The results also reveal that even though there is no determinant variable, gender, the scarce presence of Geography subjects in the Spanish education system and the education level of the parents are some of the factors that influence the results achieved by students in a pilot test on which our research is based.
Keywords: teacher training; minimum knowledge; Geography; Balearic Islands